Pemutusan Hubungan Kerja Yang Dilakukan Pelaku Usaha Kepada Tenaga Kerja Melalui Media Online Sesuai Dengan Ketentuan Undang-Undang - Johnny Pieter Sual; Merry Tjoanda; Agustina Balik (PATTIMURA Law Study Review, 2023)
ABSTRACT: Unilateral termination of employment relations is absolutely not allowed and is very clear, except for certain circumstances that compel the dismissal to be carried out, as stipulated in the "Industrial Relations Dispute Settlement Law". Unilateral layoffs by PT. Ruata's work for the workforce “Mr. VG” via Whatsapp. Mr. VG” did not receive a Decree as an employee of PT. Karya Ruata, and did not sign the Collective Labor Agreement between PT. Ruata's work with the workforce of “Mr. VG”. This research uses normative juridical research methods, namely library law research and because this research is carried out by having library materials. The approach in normative research is the Statute Approach and the Conceptual Approach. In this study, a descriptive-analytical type of research will be used. The results showed that the layoffs carried out by PT. Ruata's work to “Mr. VG” through online media (Whatsapp) is not in accordance with the provisions of the law. Article 81 number 43 of the Job Creation Law. PT Karya Ruata is not responsible for the unilateral termination of “Mr. VG” Through Online Media (Whatsapp). The unilateral dismissal action, clearly based on Article 1320 of the Civil Code, does not meet the objective requirements for the implementation of the agreement, namely the causa conditions that are allowed, so that the termination action is null and void by law. As a result of being null and void, the said dismissal by law is deemed to have never happened and therefore “Mr. VG” remains united as an employee of PT. Ruata's work, but until now “Mr. VG” is no longer working for PT. Ruata's work, and there is no settlement according to the provisions of the law.